Analisis Faktor – Faktor Yang Mempengaruhi Prestasi Belajar Dengan Menggunakan Metode Regresi Logistik Biner - Siti Hanifah; Dewi Purnama Sari (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
This research aims to know what factors will affect achievement student who study with boarding school system, by “using binary logistic regression method”, this method used for determining opportunities students who will obtain scores below then 7,5, furthermore can be used for analyze element which can be affect for student performance both internal factors although external factors. Internal factors came from oneself whereas external factors came from surroundings students such as, neighborhood, school, or family. Population on this research taken from student who study in Al-Kautsar Islamic boarding school in the school year from 2021 until 2022. This research used method by survey to Pondok Pesantren Al-Kautsar boarding school and giving them questionnaire paper to each student. The questionnaire contains X variable which is a factor that will be affected to learning achievement with independent variable parent’s education, duration of study, how many memorizations, sequence of family member, student status, intension of parents visiting, gender, and the last is student allowance. And for Y variable with data retrieval directly with responsible teacher. Software that used in this research is SPSS, classification determination model is 76,9% this results obtained with “Binary Logistic Regression”